Activation of GABA type A receptor is involved in the anti-insomnia effect of Huanglian Wendan Decoction - Liang Li; Xiaorong Wu; Xiaorong Wu; Jili Gong; Jili Gong; Zhuqiang Wang; Weibo Dai; Li Qiu; Li Qiu; Hongyuan Zuo; Mengqin Yi; Hui Yuan; et al. (Frontiers Media S.A., 2024)
Huanglian Wendan Decoction (HWD) is a traditional Chinese medicine (TCM) prescribed to patients diagnosed with insomnia, which can achieve excellent therapeutic outcomes. As positively modulating the γ-aminobutyric acid (GABA) type A receptors (GABAARs) is the most effective strategy to manage insomnia, this study aimed to investigate whether the activation of GABAARs is involved in the anti-insomnia effect of HWD. We assessed the metabolites of HWD using LC/MS and the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and tested the pharmacological activity in vitro and in vivo using whole-cell patch clamp and insomnia zebrafish model. In HEK293 cells expressing α1β3γ2L GABAARs, HWD effectively increased the GABA-induced currents and could induce GABAAR-mediated currents independent of the application of GABA. In the LC-MS (QToF) assay, 31 metabolites were discovered in negative ion modes and 37 metabolites were found in positive ion modes, but neither three selected active metabolites, Danshensu, Coptisine, or Dihydromyricetin, showed potentiating effects on GABA currents. 62 active metabolites of the seven botanical drugs were collected based on the TCMSP database and 19 of them were selected for patch-clamp verification according to the virtual docking simulations and other parameters. At a concentration of 100 μM, GABA-induced currents were increased by (+)-Cuparene (278.80% ± 19.13%), Ethyl glucoside (225.40% ± 21.77%), and β-Caryophyllene (290.11% ± 17.71%). In addition, (+)-Cuparene, Ethyl glucoside, and β-Caryophyllene could also serve as positive allosteric modulators (PAMs) and shifted the GABA dose-response curve (DRC) leftward significantly. In the PCPA-induced zebrafish model, Ethyl glucoside showed anti-insomnia effects at concentrations of 100 μM. In this research, we demonstrated that the activation of GABAARs was involved in the anti-insomnia effect of HWD, and Ethyl glucoside might be a key metabolite in treating insomnia.